INCIDENCE OF POST TRAUMATIC HYDROCEPHALUS IN PATIENTS UNDERGOING DECOMPRESSIVE CRANIECTOMY - MATEEN , U; JUMMANI , MM; SHAUKAT , S; BHATTI , T; ZULQARNAIN, .; FATIMA , K; KHAN , AA (Biological and Clinical Sciences Research Journal, 2024)
Decompressive craniectomy is a surgical procedure often employed in traumatic brain injury cases to alleviate intracranial pressure. Post-traumatic hydrocephalus, though a rare complication, can occur following this procedure, significantly impacting patient outcomes. Objective: This study aimed to investigate the incidence of post-traumatic hydrocephalus in patients undergoing decompressive craniectomy. Methods: A prospective cross-sectional study was conducted at the Emergency and Neurosurgery Department of Shaheed Mohtarma Benazir Bhutto Trauma Centre (SMBBIT) from June 1, 2022, to December 30, 2022. Demographic and clinical data were collected, including age, gender, Glasgow Coma Scale (GCS) at presentation and time of decompressive craniectomy, type of craniectomy, development of postoperative hydrocephalus, and complications. Results: The majority of patients (55%) were aged 10-15, with males comprising 75% of the cohort. Upon emergency presentation, only 4% of patients exhibited hydrocephalus, with most presenting a GCS between 9 and 13 (56%). Post-craniectomy, hydrocephalus developed in 32% of individuals, with the majority (18%) experiencing onset after 14 days. Significant associations were found between hydrocephalus development and craniectomy size (p=0.04) and distance from the midline (p=0.05). Conclusion: Patients undergoing decompressive craniectomy, particularly those with a superior limit too close to the midline, may be at risk of developing hydrocephalus. Therefore, we advocate for broader craniectomies exceeding 25 mm from the midline to potentially reduce the incidence of post-traumatic hydrocephalus and improve patient outcomes.